Comparative analysis of similarity levels between texts generated by ChatGPT-3.5 and human texts through Turnitin Software evaluation - Obando Zambrano, Beyker Stefan (2024)
The research focused on identifying the degree of similarity between documents generated by the generative artificial intelligence ChatGPT-3.5 and those created without its assistance, comparing them with the documents available in the Turnitin software databases. To achieve this objective, a descriptive research study with a quantitative approach was conducted, evaluating a total of 300 documents: 150 created entirely by ChatGPT-3.5 and 150 without the use of technological tools. These documents were produced by students from the University of Costa Rica, Guanacaste Campus, and uploaded to the Moodle platform in a space enabled with Turnitin software during the first semester of 2023. The results showed that the documents generated by ChatGPT-3.5 had an average similarity level of 22% with respect to the Turnitin system databases, significantly lower compared to the documents created without its intervention, which had an average similarity level of 33%. Additionally, the collected data indicate that, whether using generative artificial intelligence or not, it is essential to exercise caution in properly referencing documents to avoid plagiarism.